Impact Assessment of Full-converter Wind Turbine Generators Integration on Transients in Power Systems; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Askarov A. B. Alisher Bakhramzhonovich (2020, 2020)
Title screen